Taken 2 - Megaton, Olivier, 1965-; Besson, Luc; Kamen, Robert Mark; Neeson, Liam; Grace, Maggie, 1983-; Janssen, Famke, 1964-; Orser, Leland; Gries, Jon, 1957-; Sweeney, D. B. (Daniel Bernard), 1961-; Grimes, Luke, 1984-; Serbedzija, Rade, 1946-; Lacourbas, Romain; et al. (Beverly Hills, California : Twentieth Century Fox Home Entertainment, 2013)
Liam Neeson returns as Bryan Mills, an ex-CIA operative who finds himself taken hostage along with his wife. To survive, Bryan must enlist the help of an unlikely ally and use his brutally efficient skills to take out his kidnappers.
Originally released as a motion picture in 2012.
DVD release date: January 15, 2013.
Special features: Alternate ending ; FX Movie Channel presents: in character with Liam Neeson ; theatrical trailer.
Director of photography, Romain Lacourbas ; film editors, Camille Delamarre, Vincent Tabaillon ; music, Nathaniel Mechaly.
Liam Neeson, Maggie Grace, Famke Janssen, Leland Orser, Jon Gries, D.B. Sweeney, Luke Grimes, Rade Sherbedgia.
MPAA rating: PG-13; for intense sequences of violence and action, and some sensuality CHV rating: 14A.
Keywords: Kidnapping -- Drama; Kidnapping victims -- Drama; Hostages -- Drama; Feature films; Action and adventure films; Crime films; Drama; Thrillers (Motion pictures); Video recordings for people with visual disabilities; Video recordings for the hearing impaired; DVDs